PHYSIOLOGY: BASIS OF ALL MEDICAL SCIENCES - Ahmed, Umbreen (Pakistan Journal of Physiology, 2018)
Health and NOT disease is the greatest mystery of medical science. In a broader perspective Physiology is a science that deals with the normal functioning of any living organism. Given the magnitude of the subject, it is further divided into different categories including, viral physiology, bacterial physiology, plant physiology and animal physiology. Human Physiology is one of the fields of animal physiology that deals specifically with the normal functioning of human body. It explains the mechanisms involved, the cross talks and the cross linkages at subcellular and cellular level, and the pathways followed at tissue, organ and system level to maintain health. This science is the basis of all medical knowledge and is further subcategorized among others, into cellular physiology, system physiology, sports and exercise physiology, and physiology of unusual environment. Pak J Physiol 2018;14(1):1-2